2017
DOI: 10.1111/adj.12486
|View full text |Cite
|
Sign up to set email alerts
|

Potential risks of orthodontic therapy: a critical review and conceptual framework

Abstract: This review examines some of the potential risks of orthodontic therapy along with their evidence base. The risks of orthodontic treatment include periodontal damage, pain, root resorption, tooth devitalization, temporomandibular disorder, caries, speech problems and enamel damage. These risks can be understood to arise from a synergy between treatment and patient factors. In general terms, treatment factors that can influence risk include appliance type, force vectors and duration of treatment whilst relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 127 publications
(162 reference statements)
1
88
1
9
Order By: Relevance
“…Early dental caries, called white spot lesions, is the best known form of caries associated with orthodontic treatment 22 . Although the reported prevalence rates of dental caries in patients who receive orthodontic treatment vary widely 8,14,23 , younger patients are more likely to develop dental caries because of their immature tooth enamel and lack of appropriate oral hygiene 3,22 . A previous study 24 found that the prevalence of orthodontic treatment-related dental caries was higher in male patients than in female patients, while another study 22 found no significant sex-related difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early dental caries, called white spot lesions, is the best known form of caries associated with orthodontic treatment 22 . Although the reported prevalence rates of dental caries in patients who receive orthodontic treatment vary widely 8,14,23 , younger patients are more likely to develop dental caries because of their immature tooth enamel and lack of appropriate oral hygiene 3,22 . A previous study 24 found that the prevalence of orthodontic treatment-related dental caries was higher in male patients than in female patients, while another study 22 found no significant sex-related difference.…”
Section: Discussionmentioning
confidence: 99%
“…However, orthodontic treatment can have undesirable consequences, including periodontal disease, root resorption, tooth devitalisation, temporomandibular disorder, caries and damage to enamel 2,3 . However, orthodontic treatment can have undesirable consequences, including periodontal disease, root resorption, tooth devitalisation, temporomandibular disorder, caries and damage to enamel 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, orthodontic treatment can cause some potential risks and complications, because teeth undergone orthodontic movement may have resorption of cementum and dentine [13]. On the other hand, in some patients, it is impossible to insert even SDIs after orthodontic treatment because of the apices of the adjacent teeth roots.…”
Section: Discussionmentioning
confidence: 99%